Strategi Manajemen Event Pertandingan Olahraga di Masa Pandemi Covid-19 pada Pengurus KONI Provinsi Jawa Timur - Maruta, Ramadhan; Erta, Erta; Indarwati, Tias Andarini; Primanata, Dani; Puspita, Hapsari Shinta Citra (Journal of Sport Science and Education, 2022)
Competition activities in large sports competitions require a good management in their management. Good management will support the process of running an event that will be organized by KONI of East Java Province. As a sports committee body that oversees all sports at the level of the province of East Java, which will carry out several events to screen regional athletes who will compete at the National and International levels. Several matches have been arranged and scheduled for one year in a row to meet the needs of qualified regional athletes. The Covid-19 pandemic has forced several match schedules to be shifted and canceled due to impossible conditions. Uncertain circumstances make the management revolution to make the right planning in changing and determining the schedule of sports matches so that there is no big loss when a match is postponed or canceled. . Based on the results of the research, several themes are produced, namely good planning that will minimize the occurrence of risk, organizing the division of tasks to speed up work, actuality of practical implementation of sporting events, and control to improve quality. Careful planning and implementation can make it easier to manage the management of sporting events during the Pandemic.